A study on the physical Insults on drugs For forensic investigation - Bakar, Nur Syafawati Abu (2020)
Drug is medicine or substance which have its effect when it introduced to the body. It was designed in natural or synthetic substance to produce a specific set of psychological effects on the human body or animals but when it misused, it’s become unlawful which called an illicit drug. The World Drug Report (2019) was reported a global overview of the latest estimates and trends in the supply, use and health consequences of illicit drugs. It represents the largest volume of criminal cases examined by forensic science laboratories. This study was aimed at determining the effect of physical insults on the detection of drugs. Paracetamol (PCM) is one of the possible adulterants in illicit drugs such as cocaine and heroin. In this study, seventytwo samples from two brands of paracetamol were examined physically to determine their colours, weight and dimension. Packaged using respective glass containers, plastic bag and paper wrap, and were exposed to four types of physical insults including shaking, putting in the car, handbag and pocket pants. Any physical changes due to physical insults were determined. All packaging materials were also extracted and analysed using gas chromatography - flame ionisation detection (GC-FID) to detect the presence of paracetamol. From this study, it was shown that the types of packaging and the physical insult could change the physical characteristics of the tablets drugs. Packaging the drugs in glass containers introduced more insults to the drug samples as compared to other types of packaging. In terms of physical insults, the presence of drugs possessed a high possibility to be detected on those containers used to keep the drugs. On the other side, it is not good for drug packaging because it introduces to sample damage. Besides, the paper used to wrap the tablet drugs were detected with drugs when they are kept in the pocket pants for a duration of time compared to the plastic bag which introduces less in physical insult. Plastic bag is the best type of packaging for a drug. This comparative information had offered beneficial information in forensic investigation to identify the forensic evidence with high potential to give a positive indication of drugs, as well as the most appropriate procedure in drug handling to maximise the detection of drugs.